LEGAL FEATURES OF BUILDING A RESIDENTIAL BUILDING ON THE BASIS OF A BUILDING PASSPORT - Рябова, Катерина Олексіївна; Майстров, Денис Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Aim: the article is devoted to the analysis of the maximum allowable area of a residential building, which can be built on the basis of a building passport, a procedure for obtaining a building passport and the introduction of a building built on the basis of a building passport in operation. Methods of research: analyzes the approaches of different scientists to determine the concept of "residential building", as well as the norms of the current legislation, regulating the legal relationship that arises when building a residential building on the basis of a building passport. Results: outline the maximum allowable area of a residential building that can be built on the basis of a building passport. Discussion: problems of domestic legislation and practices that arise during the construction of a residential building on the basis of a building passport.